Factors affecting financial investment decisions: undergraduate student context - Hidayat, Febrian Satria; Hartono, Ulil (BISMA (Bisnis dan Manajemen), 2022)
Investment decisions are decisions to allocate funds into firms of investment that will generate higher profits in the future. This study aims to examine factors affecting financial investment decisions in undergraduate student context. Undergraduate students become interesting to investigates since they started investing their monthly income. This study employs quantitative research and the structural equation model analysis method. A total of 230 undergraduate students responded to the survey. The findings of the study indicate that there are several factors which significantly affect student financial investment decision which are financial literacy, financial attitude, regret aversion bias, and herding. Risk tolerance does not influence student investment decision. Thus, this study implies the importance financial service institutions roles and universities in educating and providing insight to potential investors, i.e., undergraduate students. Efforts to improve investment decisions from an early age are essential since increasing the amount of investment is beneficial for a country's economy.